The Effect of Chlorella vulgaris on Lipid Profile Wistar Strain Rats (Rattus norvegicus Berkenhout, 1769) Under Induced Stress - Karima, Farah Nadia; Sarto, Mulyati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Stress is a psychiatric/psychological disorder characterized by a sense of disability, despair, anhedonia, decreased activity, and pessimism. Stress can affect the physiological condition of the body with symptoms of lipid metabolism disorders. Chlorella vulgaris is a microalgae that is known to have the potential as an alternative antidepressant drug. The study was conducted to determine the lipid profile of blood wistar strain rats after stress induction and the effect of administration of Chlorella vulgaris on blood lipid profiles of stress-induced wistar rats. This research is an experimental study using 5 treatments with 25 models of Rattus norvegicus wistar strain, 2 months old. The treatment group consisted of 1 control group, 1 stress group, and 3 groups of treatment variations, namely the treatment of antidepressant medication, the treatment of administration of cultivated Chlorella vulgaris, and the treatment of commercial Chlorella. Stress induction is carried out by treatments that given to the rats randomly, namely cold water, warm water, wet cage, dark-light cycle, and sound wave exposure for 40 days. Examination of blood lipid profiles was carried out on Day 0 after mice were acclimated, day 40 after rats were induced stress, and day 56 after rats were given treatment of cultivated Chlorella vulgaris. The results obtained were the stress conditions of the lipid profile of the wistar strain of rats which had increased were total cholesterol levels of the control group and triglyceride levels in all groups while those who had decreased were cholesterol levels other than the control group, HDL levels in all groups, and LDL levels all groups. Giving Chlorella vulgaris had effect on decreasing total cholesterol levels, triglyceride levels, and LDL levels along with increasing HDL levels.